Shear buckling of ship plates with different holes - Zhu Zhaoyi; Li Xiaowen; Chen Qinglin; Cai Yingqiang (Mechanics & Industry, 2022)
Based on the first-order shear deformation theory, numerical methods and mechanical experiments, the shear buckling characteristics of hull plates with different holes are investigated. Through eigenvalue buckling analysis, the critical buckling stress of square plate with hole under uniform shear load on four edges was calculated. The relationship between the critical shear stress and the hole type, hole size and plate thickness was obtained by parameterization. The reduction coefficient (ki) was defined to characterize the effect of the hole on the plate, and the reduction effect of circular hole, square hole and fillet square hole was simplified by graph and fitting polynomial. The results show that the critical buckling shear stress obtained from numerical simulation is in good agreement with the experimental value. For different types of holes, the critical buckling shear stress of the square plate has the same trend with the plate thickness. Both plate thickness and hole size have great influence on the shear stability of the perforated square plate. When the hole size is constant, the critical shear stress increases with the increase of plate thickness. The smaller the hole size is, the greater the influence of plate thickness. The critical shear stress decreases with the increase of hole size, and there is a similar linear relationship. The smaller the plate thickness, the more obvious the linear relationship. In addition, based on the reduction coefficient curve or fitting polynomial proposed in this paper, the influence rules of the three different holes on the shear stability of hull plates can be obtained quickly and effectively, thus providing a useful reference for the design optimization and mechanical property evaluation of ship structures with holes.